GRAY CORRELATION ANALYSIS OF SURFACE INTEGRITY OF ULTRASONIC-ASSISTED ROLLING GCR15 BEARING STEEL - LEI Jun; SU YongXiang; XU QingJun (Jixie qiangdu)
In order to achieve reasonable control of the surface integrity of the workpiece assisted by ultrasonic-assisted rolling. Taking GCr15 bearing steel as the research object,the rotational speed,feed rate and static pressure were selected as the main processing parameters. The ultrasonic-assisted rolling test was used to combine the gray theory,response surface method and genetic algorithm to ultrasonically assisted rolling GCr15 bearing steel. Correlation analysis was carried out on surface roughness,residual stress and hardness,and a grey correlation degree prediction model was established,and the model was optimized. The results show that the static pressure has the greatest influence on the surface integrity of the ultrasonic assisted rolling workpiece,the second speed and the minimum feed rate; the optimal processing parameters are the feed speed 25 mm/min,the speed 300 r/min,the static pressure 247 N; The corresponding surface roughness was 0. 299 μm,the residual stress was-376. 4 N,and the hardness was 759. 8 HV. The research results have important engineering significance for improving the surface integrity of ultrasonic assisted rolling workpieces and determining the optimal ultrasonic assisted rolling processing parameters.